Type Analysis of Speaking Performance Assessment Task in English for Nusantara Textbook - Dewantara, Kadek Andre Karisma (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
One of the key factors in the success of learning English is the use of textbooks. The English textbook entitled "English for Nusantara SMP/MTs Class VIII" is one of the textbooks used in many schools as a guide for teachers and students in teaching and learning English. Although English for Nusantara textbooks have been widely used, there is no research has focused on the analysis of speaking assessment tasks in this textbook. Therefore this study aims to analyze the task of assessing speaking skills in Nusantara English textbooks. This study use a qualitative approach. The subject of this research is Nusantara English textbooks used in the context of learning English in Indonesia. Data collected through document analysis will include task descriptions, types of assessment, and instructions given for each task. The collected data will be analyzed descriptively to identify the types of assessment included in the speaking tasks. The results of this study show that intensive assessment tasks are the most common in this book. However, this study also found a limited variety of activities in speaking assessment task. The implications of the results of this research are important in the development of textbooks and the improvement of learning speaking skills in the context of English in Indonesia.